ANALISA FAKTOR-FAKTOR YANG MEMPENGARUHI PERSEPSI KONSUMEN DALAM PEMILIHAN BIRO PERJALANAN UMROH DAN HAJI KHUSUS - Mohammad Savier Azmy; Asnan Furinto (Journal of Business Strategy and Execution, 2008)
Purpose of research is to identified the factors which influence the consumer perception in choosing Biro Perjalanan Umroh and Haji Khusus with moderating experience variable of Hajj and Umra. The factors that can be identified are Brand Equity, Guide, Reference, Quality Offering, Confidence Benefit, Special Treatment Benefit, Social Benefit, Religious Congruence as a independent variable, and Perceived Comfort, Perceived Affiliation as a dependent variable. The method that will be use is Analysis Factor method and linear regression with software SPSS 11.0. Result of research is after repeated the analysis factors with rotation, and then formatted 3 factors such as: Attributes factors: Brand Equity, Guide, Reference, Quality Offering and Confidence Benefit Search of Community Factors: Religious Congruence and Perceived Affiliation. Exclusivity Factors: Special Treatment and Perceived Comfort Brand Equity variable, Reference, Quality Offering, Confidence Benefit and Special Treatment Benefit was proven influencing Perceived Comfort variable.  Whereas variable Guide wasn’t proven influencing Perceived Comfort variable. Religious Congruence variable was proven influencing Perceived Affiliation variable. Whereas Social Benefit variable wasn’t proven influencing Perceived Affiliation variable. Guide variable, Quality Offering and Confidence Benefit for experienced consumer in Umra and Hajj wasn’t proven influencing more Perceived Comfort, comparing with inexperienced in Umra and Hajj using Biro Perjalanan Umroh and Haji Khusus. Social Benefit variable for experienced consumer in Umra and Hajj (Experience of Hajj & Umra) wasn’t proven influencing more Perceived Affiliation, Comparing with inexperienced consumer in Umra and Hajj using Biro Perjalanan Umroh and Haji Khusus.